Robo sacer : necroliberalism and cyborg resistance in Mexican and Chicanx dystopias - Dalton, David S. (Critical Mexican studies., 2023)
The resistant potential that arises when the oppressed use technology to undermine the social hierarchies inherent to global capitalism.